Physical and Electrochemical Properties of Ionic Liquids Based on Quaternary Phosphonium Cations and Carboxylate Anions as Electrolytes. (10th January 2017) - Shimada, Jin; Tsunashima, Katsuhiko; Ue, Mayu; Iwasaki, Kazuki; Tsuda, Tetsuya; Kuwabata, Susumu; Kanematsu, Hideyuki; Hirai, Nobumitsu; Kogo, Takeshi; Ogawa, Akiko
Abstract : A new group of ionic liquids based on tetraethylphosphonium and tetrabutylphosphonium cations together with several carboxylate anions is proposed and presented in this report. In obtained ionic liquids, tetrabutylphosphonium formate and tetrabutyl-phosphonium lactate became room temperature ionic liquids. It was found that the phosphonium ionic liquids showed the typical VTF-type convex curve behaviors. The phosphonium ionic liquids also had a high cathodic stability similar to those of the TFSA- and FSA-anion based phosphonium ionic liquids. On the other hand, relatively low anodic potential window was observed. The thermal stability of the phosphonium ionic liquids showed higher thermal stabilities than those of the corresponding ammonium ionic liquids.